Pengembangan Strategi Blended Learning Sebagai Pendukung Perkuliahan Mahasiswa Milenial - Faridatun Nadziroh; Handi Rahmannuri; Evy Nur Amalina (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2019)
At present, the development of learning patterns for students needs to be considered. The rapid advancement of technology requires educators, especially lecturers to provide new strategies to be able to help increase students' interest in learning, especially millennial students who are starting to decreased. Millennial students more interested to want a learning model that is practical and not boring. This is what drives the writer to conduct research that focuses on learning models that are not only face-to-face in the classroom but can be done anywhere and anytime. The author choose blended learning as an applied learning model because this model is a combination of face-to-face learning and computer-based learning. The development of this model utilizes based on social media edmodo for education. The object of the study was conducted on two classes of word processing courses on office automation students ini AKSI Gresik. The object of research was 39 millenial students. The results obtained from the pretest and posttest there are significant differences in the average range of values obtained. Where at the time of the pretest the value entered in the interval 69 ≤ value ≤ 84 with good criteria. while at posttest the value entered in the interval of 85 ≤ value ≤ 100 with very good criteria. Keywords : Blended Learning, Learning Interest, Millenial Student